1991
DOI: 10.1002/ajmg.1320410122
|View full text |Cite
|
Sign up to set email alerts
|

Glutaric aciduria type I: A common cause of episodic encephalopathy and spastic paralysis in the Amish of Lancaster County, Pennsylvania

Abstract: We have diagnosed type I glutaric aciduria (GA-I) in 14 children from 7 Old Order Amish families in Lancaster County, Pennsylvania. An otherwise rare disorder, GA-I appears to be a common cause of acute encephalopathy and cerebral palsy among the Amish. The natural history of the disease, which was previously unrecognized in this population, is remarkably variable and ranges from acute infantile encephalopathy and sudden death to static extrapyramidal cerebral palsy to normal adult. Ten patients first manifest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
71
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(75 citation statements)
references
References 17 publications
4
71
0
Order By: Relevance
“…Deficiency of GCDH causes increased organic acid excretion of glutaric acid, 3-hydroxyglutaric acid and glutaconic acid in urine and elevated glutarylcarnitine (C5DC) in plasma. The estimated worldwide frequency of GA I is 1 in 100,000 newborns (Lindner et al 2004), but increased frequency has been reported in the inbred Old-Order Amish community of Pennsylvania (Morton et al 1991) and the Ojibway Indians in Manitoba (Haworth et al 1991). About ninety percent of the affected children present classically between 2 and 37 months of age with extrapyramidal symptoms, predominantly dystonia superimposed on axial hypotonia after an acute encephalopathic crisis precipitated by intercurrent febrile illness, infection, fasting or immunization (Hoffmann et al 1991;Kolker et al 2006;Strauss et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Deficiency of GCDH causes increased organic acid excretion of glutaric acid, 3-hydroxyglutaric acid and glutaconic acid in urine and elevated glutarylcarnitine (C5DC) in plasma. The estimated worldwide frequency of GA I is 1 in 100,000 newborns (Lindner et al 2004), but increased frequency has been reported in the inbred Old-Order Amish community of Pennsylvania (Morton et al 1991) and the Ojibway Indians in Manitoba (Haworth et al 1991). About ninety percent of the affected children present classically between 2 and 37 months of age with extrapyramidal symptoms, predominantly dystonia superimposed on axial hypotonia after an acute encephalopathic crisis precipitated by intercurrent febrile illness, infection, fasting or immunization (Hoffmann et al 1991;Kolker et al 2006;Strauss et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Often in cases of GA-I, the molar ratio of C5DC to C16 is also increased, thus becoming another criterion for identifying presumptive cases. Relatively rare in the general population, GA-I occurs more frequently in populations that are more commonly consanguineous, such as the Amish of Lancaster County, PA (119 ), and the Canadian aborigines of Manitoba/Northwestern Ontario (120 ). Infants with MADD or GA-II may also have increased C5DC.…”
Section: -Hydroxyisovalerylcarnitine (C5oh)mentioning
confidence: 99%
“…Prevalence has been variably estimated between 1:100,000 and 1:30,000 in different studies and populations (Strauss et al 2003;K€ olker et al 2006a. Incidence is highest in certain genetically homogeneous communities such as the Old Order Amish of Lancaster County, Pennsylvania (1 in 300-400 newborns), and the aboriginal Ojibway-Cree Indians of Northern Canada (1 in 300 newborns) where common mutations in homozygous state are often found (Morton et al 1991;Haworth et al 1991). The GCDH gene is located on chromosome 19p13.2, is 7 kb large, contains 11 exons and 10 introns, and codes for a polypeptide product of 438 amino acids, from which the functional GCDH is derived after cleavage of the 44-amino acids N-terminal targeting sequence following import into the mitochondrial matrix (Koeller et al 1995;Schwartz et al 1998).…”
Section: Introductionmentioning
confidence: 99%